Determinants of E-commerce in Marketing: A Case of Kathmandu Valley - Majgainya, Sumit Sharma (Nepalese Journal of Business, 2024)
This study examines the determinants of e-commerce in marketing in the context of Kathmandu Valley. The dependent variable of the study is e-commerce. Similarly, the selected independent variables are customer satisfaction, tailoring, convenience, productivity, phase allowing order and campaign. The primary source of data is used to assess the opinions of the respondents regarding customer satisfaction, tailoring, convenience, productivity, phase allowing order, campaign and e-commerce. The study is based on primary data of 110 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different determinants of e-commerce in marketing. The study showed that customer satisfaction has a positive impact on e-commerce. It indicates that higher the level of customer satisfaction, higher would be the use of e-commerce. Similarly, tailoring has a positive impact on e-commerce. It indicates that increase in tailoring leads to increase in the use of e-commerce. Likewise, convenience has a positive impact on e-commerce. It indicates that increase in convenience leads to increase in the use of e-commerce. In addition, productivity has a positive impact on e-commerce. It indicates that higher the productivity, higher would be the use of e-commerce. Further, phase allowing order has a positive impact on e-commerce. It indicates that easy phase allowing order leads to increase in the use of e-commerce. Likewise, campaign has a positive impact on e-commerce. It indicates that increase in campaign leads to increase in the use of e-commerce.